DAMPAK PERUBAHAN IKLIM GLOBAL TERHADAP KESEHATAN MASYARAKAT DI INDONESIA - Khoiron, Khoiron (FKM - UNEJ, 2009)
Climate change occurred in many areas in all over the world, have closely relationship with public health. The climate change brought damage for peopleâs live. Climate change caused by adding of greenhouse gases (carbon dioxide, methane, nitrous oxide). On the Â other hands, people can cause increase of greenhouse gases. This paperÂ discusses relationship between climate change and public health, in the sense of climate changeâs âcontributionsâ to environment change, which leads to climate change and another way around the impact of climate change to the public health situation. Evidences from many regions show that climate change caused disasters and extreme weather. Disaster and extreme weather caused death, food scarcity, malnutrition, scarcity of fresh water, hence poor sanitation, change in vector prevalence, air pollution rises, and health risk with additional climate related disease burdens. On another side, some human cause climate change occurred through peopleâs practices of habbitsÂ and behaviors that caused increasing of greenhouse gases. Their practices ofÂ felling forest trees excessively and forest burning that caused deforestations, treatment of municipal waste with open dumping method, and used fossil energy excessively. Key words : impact, global climate change, public health